2013
DOI: 10.1111/jgs.12458
|View full text |Cite
|
Sign up to set email alerts
|

Nonmotor Symptoms in Nursing Home Residents with Parkinson's Disease: Prevalence and Effect on Quality of Life

Abstract: Nonmotor symptoms were highly prevalent in NH residents with PD. Quality of life was poor, largely because of NMS. Because many NMS are potentially treatable, diagnosis and treatment of these severely affected individuals deserve more attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 48 publications
3
43
0
3
Order By: Relevance
“…This study was carried out in ambulatory patients treated in primary care facilities, in an early disease stage. In populations of late-stage PD patients living in nursing care facilities, 77 % of patients were found to meet criteria for PD-related dementia, and besides cognitive complaints, depression and poor nighttime sleep were also found frequently [13]. Gender differences have also been described.…”
Section: Discussionmentioning
confidence: 96%
“…This study was carried out in ambulatory patients treated in primary care facilities, in an early disease stage. In populations of late-stage PD patients living in nursing care facilities, 77 % of patients were found to meet criteria for PD-related dementia, and besides cognitive complaints, depression and poor nighttime sleep were also found frequently [13]. Gender differences have also been described.…”
Section: Discussionmentioning
confidence: 96%
“…This study is first of all mainly focused on patients with PD living independently at home. Two patients in a nursing home were spoken to and it was decided not to include more nursing home patient as their perceptions on QoL had already been studied [39]. However, when comparing the member check reports of the PD patients living in a nursing home with other participants in the study, it was concluded that their perceptions might not vary much.…”
Section: Discussionmentioning
confidence: 97%
“…Another study demonstrated that PD patients with Hoehn &Yahr stage 4 had significantly more daytime sleepiness than stages 1, 2, or 3, without group differences for dopaminergic therapy[301]. In a study of non-motor symptoms in nursing home residents with PD, 68% reported daytime sleepiness[295], supporting the idea that EDS is related to disease duration and severity.…”
Section: Excessive Daytime Sleepinessmentioning
confidence: 99%